ISLAM EKSKLUSIF YANG TOLERAN: TELAAH ATAS POLA DIDAKTIS ADIT SOPO JARWO - Yulianto, Wawan Eko (ATAVISME, 2018)
Adit Sopo Jarwo is an Indonesian animation series that has gained quite high popularity in the past couple of years. However, there is still some dissatisfaction among its audience regarding the series? overtly didactic nature. This study aims to highlight and explain the didactic pattern of Adit Sopo Jarwo and to interpret this didacticism with regards to the social context that serves as the background of this work. For the purpose of this study, ten episodes of Adit Sopo Jarwo obtained from a YouTube search were analyzed. This study reveals the monolithic tendency of the didacticism of Adit Sopo Jarwo with the involvement of Haji Udin both direct and indirect as the source of wisdom. In the final analysis, the writer proposes the hypothesis of exclusivist but tolerant Islam as the explanation for the didactic pattern of Adit Sopo Jarwo.